Examining the impact of social media on consumer perception of corporate reputation - Dong, Huiyun (2017)
Purpose: This study aims to examine the impact of social media on consumer perception of corporate reputation which measured by four related variables (products and services, customer attitude, customer relationship and corporate social responsibility).